The Effectiveness of Multiliteracy Pedagogy in Teaching Writing Explanation Texts to Senior High School Students - Dalia, Arisa Cahyalaili; Jamilah, Jamilah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigate the effectiveness of multiliteracy pedagogy in teaching writing explanation texts to senior high school students, focuses on teaching students’ writing skills on explanation texts which aims to find out whether there is a significant difference between students who use multiliteracy pedagogy and those who do not use multiliteracy pedagogy. The quantitative research in a quasi-experimental approah was employed 42 students in two groups participating, the control group and the experimental group. The data collection techniques used were pre-test, post-test, and explanation texts writing tests asresearch instruments. The data were analyzed using SPSS version 25, Shapiro-Wilk for the normality test, Lavene test for the homogenity test, Independent sample t-tests and paired sample t-tests were used to find data differences. The findings reveal a significant difference between the control and experimental classes, with the control class’s score of 77.33 on the post-test and the experimental class’s score of 80.62. The study reveals that using multiliteracy pedagogy is more effective than using conventional learning in teaching writing explanation text. The independent sample t-test results showed that the Sig. 0.044 lower than 0.05 means that there is a significant difference between the average results of writing explanation texts in the experimental group and the control group. Therefore, the multiliteracy pedagogy has been proven effective in improving students’ writing ability in explanation text in eleventh grade at Kahar Rahman Islamic Boarding school.